A Comparative Study of Higher Education Entrance Examinations in Iran with Some Selected Countries - Narges Moradi; Reza Mohammadi; Akber Goldasteh (Comparative Education Society of Iran ( CESIR), 2019)
The main purpose of this article is a comparative study of Higher Education Entrance Examinations in selected countries in order to optimize the national examination in Iran. The present study is a qualitative, non-experimental, and comparative research. Country selection strategy is "most different system" according to Bray and Thomas Cube and level of analysis and observation is intercontinental. The statistical population included all higher education systems with similar assessment and admission systems. The countries under study were selected through Targeted Sampling Technique and are Australia, Brazil, China, England, Japan, Netherlands, Nigeria, and Turkey. Data were collected by studying the official website of assessment centers, universities and government documents. The findings show that in Iran and Turkey, there are two separate ministries for formal and general education and higher education, while in other countries this is responsibility of one ministry. Also, Iran and Turkey have centralized examination and admission while other countries have centralized entrance examination but decentralized admission. In terms of type of examination, Iran has an entrance exam based on four-choice questions that will be held within a half day. According to the research findings and in order to optimize the national examination in Iran, it is suggested that a national specialized organization be established to prepare, measure and validate the entrance examination to higher education institutions. It is also recommended to design tests and questions appropriate to each field, use short answer tests, hold multiple national examinations throughout the year and validate the test results every two year.